circ-Sirt1 Decelerates Senescence by Inhibiting p53 Activation in Vascular Smooth Muscle Cells, Ameliorating Neointima Formation - Kong, Peng; Li, Chang-Lin; Dou, Yong-Qing; Cao, Li; Zhang, Xiao-Yun; Zhang, Wen-Di; Bi, Ze-Qi; Peng, Zu-Yi; Yan, An-Qi; Han, Mei (Frontiers in Cardiovascular Medicine, 2021)
Vascular smooth muscle cell (VSMC) senescence is a major driver of neointimal formation. We have demonstrated that circ-Sirt1 derived from the SIRT1 gene suppressed VSMC inflammation and neointimal formation. However, the effect of circ-Sirt1 inhibiting inflammation on VSMC senescence during neointimal hyperplasia remains to be elucidated. Here, we showed that circ-Sirt1 was highly expressed in young and healthy arteries, which was decreased in aged arteries and neointima of humans and mice. Overexpression of circ-Sirt1 delayed Ang II-induced VSMC senescence in vitro and ameliorated neointimal hyperplasia in vivo. Mechanically, circ-Sirt1 inhibited p53 activity at the levels of transcription and post-translation modulation. In detail, circ-Sirt1, on the one hand, interacted with and held p53 to block its nuclear translocation, and on the other hand, promoted SIRT1-mediated p53 deacetylation and inactivation. In conclusion, our data suggest that circ-Sirt1 is a novel p53 repressor in response senescence-inducing stimuli, and targeting circ-Sirt1 may be a promising approach to ameliorating aging-related vascular disease.